2011
DOI: 10.4319/lo.2011.56.3.0787
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biological processes underlying the sudden surface appearance of a red tide in the nearshore

Abstract: The sudden appearance at the surface of an alongshore-parallel band of red tide near Huntington Beach, California, is described in high spatial and temporal resolution using novel instrumentation including a global positioning system-tracked jet-ski. The scale of the surface chlorophyll a (Chl a) band was small (, 200 m crossshore) and ephemeral (3 h) compared with the subsurface extent of the red tide (, 2 km, . 7 d). The red tide was dominated by the regionally common dinoflagellate Lingulodinium polyedrum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 38 publications
(39 reference statements)
2
43
0
Order By: Relevance
“…Flow is onshore near the surface over the shoals ) and if near surface concentrations of cells are lower than in the water column then the concentration of phytoplankton in the water entering the surface zone over the shoals may simply reflect the low near surface cell concentration. Where waves impinge at an angle to a more dissipative surf zone, rip currents do not form; rather an alongshore current is generated within the surf zone (Omand et al, 2011). In this situation, without rip currents, a phytoplankton bloom on the inner shelf did not enter the surf zone (Omand et al, 2011), a result similar to what we observed at the CRSB reflective surf zone.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Flow is onshore near the surface over the shoals ) and if near surface concentrations of cells are lower than in the water column then the concentration of phytoplankton in the water entering the surface zone over the shoals may simply reflect the low near surface cell concentration. Where waves impinge at an angle to a more dissipative surf zone, rip currents do not form; rather an alongshore current is generated within the surf zone (Omand et al, 2011). In this situation, without rip currents, a phytoplankton bloom on the inner shelf did not enter the surf zone (Omand et al, 2011), a result similar to what we observed at the CRSB reflective surf zone.…”
Section: Discussionsupporting
confidence: 76%
“…Where waves impinge at an angle to a more dissipative surf zone, rip currents do not form; rather an alongshore current is generated within the surf zone (Omand et al, 2011). In this situation, without rip currents, a phytoplankton bloom on the inner shelf did not enter the surf zone (Omand et al, 2011), a result similar to what we observed at the CRSB reflective surf zone. Without rip currents, dissipative and intermediate surf zones may behave like the sampled reflective surf zone.…”
Section: Discussionsupporting
confidence: 76%
“…Moored observations-A cross-shore transect of moorings, paired with bottom or surface-mounted current meters spanning H 5 8-59 m, was deployed (Omand et al 2011). Data from a subset of these instruments are discussed here.…”
Section: Methodsmentioning
confidence: 99%
“…The amplitude of these internal waves varies directly with the amplitude of the surface tides; larger surface tides generate larger internal waves (Winant 1974, Holloway et al 1997, Trevorrow 1998. The internal tides can transport both larvae (Shanks 1983, 1988, Kingsford & Choat 1986, Pineda 1991, 1994, Leichter et al 1998) and phytoplankton shoreward (Omand et al 2011). Shanks & McCulloch (2003) found that peaks in abundance of Pseudo-nitzschia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Ryan et al (2005) described the concentration of a dino flagellate bloom by the pas sage of large internal waves in Monterey Bay, Cali fornia (USA); the very high concentration of phytoplankton in the internal waves suggested that transport of phytoplankton occurred. Omand et al (2011) presented a detailed description of the transport of a dinoflagellate bloom to the shore by internal waves.…”
Section: Introductionmentioning
confidence: 99%